Association of phenylalanine and tyrosine metabolism with mortality and response to nutritional support among patients at nutritional risk: a secondary analysis of the randomized clinical trial EFFORT - Buchmueller, Lena C.; Wunderle, Carla; Laager, Rahel; Bernasconi, Luca; Neyer, Peter J.; Tribolet, Pascal; Stanga, Zeno; Mueller, Beat; Schuetz, Philipp (Frontiers in Nutrition, 2024)
Background: Elevated phenylalanine serum level is a surrogate marker of whole-body proteolysis and has been associated with increased mortality in critically ill patients. Tyrosine is a metabolite of phenylalanine and serves as a precursor of thyroid hormones and catecholamines with important functions in the oxidative stress response among others. Herein, we examined the prognostic significance of phenylalanine, tyrosine, as well as its metabolites nitrotyrosine, L-3,4dihydroxyphenylalanine (DOPA), and dopamine regarding clinical outcomes and response to nutritional therapy in patients at nutritional risk.Methods: This is a secondary analysis of the Effect of Early Nutritional Support on Frailty, Functional Outcomes, and Recovery of Malnourished Medical Inpatients Trial (EFFORT), a randomized controlled trial investigating individualized nutritional support compared to standard care in patients at risk of malnutrition. The primary outcome was 30-day all-cause mortality.We analyzed data of 238 patients and found a significant association between low plasma levels of phenylalanine (adjusted HR 2.27 (95% CI 1.29 to 3.00)) and tyrosine (adjusted HR 1.91 (95% CI 1.11 to 3.28)) with increased 30-day mortality. This association persisted over a longer period, extending to 5 years. Additionally, trends indicated elevated mortality rates among patients with low nitrotyrosine and high DOPA and dopamine levels. Patients with high tyrosine levels showed a more pronounced response to nutritional support compared to patients with low tyrosine levels (HR 0.45 versus 1.46, p for interaction = 0.02).In medical inpatients at nutritional risk, low phenylalanine and tyrosine levels were associated with increased short-and long-term mortality and patients with high tyrosine levels showed a more pronounced response to nutritional support. Further research is warranted to gain a deeper understanding of phenylalanine and tyrosine pathways, their association with clinical outcomes in patients at nutritional risk, as well as their response to nutritional therapy.